Farming Systems in Less-favored Areas: Strategies for Sustainable Resource Use and Poverty Alleviation 1 - Ruben, Ruerd (Annals of Arid Zone, 2016)
Poor people living in less-favored areas (LFAs) face the hardships of man and nature. LFAs are typically backward areas that have gained little from past agricultural successes and are characterized by widespread poverty and resource degradation. Due to the combination of the fragile natural resource base and geographical remoteness, new approaches for addressing simultaneously chronic poverty and land degradation are urgently required. Farming systems in LFAs are highly diversified" and rely on ingenious combinations of internal and external resources for creating synergies and to stabilize yields as well as returns to labor. Diversification of crop and livestock activities and selective engagement in off-farm employment represent major survival strategies. Support systems for enhancing LF A farming system development and rural livelihoods need to be based on appropriate combinations of targeted incentives and local collective action. This article provides an overview of current research and practice concerning best practice strategies for optimizing resource management and reducing poverty in LFAs. Key attention is given to options for reinforcing the productivity and resilience of farming systems and the rationale for enhancing public investment in LFAs. We argue that increasing infrastructure and input provision and delivering supportive services in LFAs is a necessary and effective strategy for reversing the spiral of poverty and resource degradation.